2010
DOI: 10.1108/17542411011081383
|View full text |Cite
|
Sign up to set email alerts
|

Gender and risk: women, risk taking and risk aversion

Abstract: PurposeLabeling women as risk‐averse limits the positive benefits both women and organizations can gain from their risk taking. The purpose of this paper is to explore women's risk taking and reasons for stereotype persistence in order to inform human resource practice and women's career development.Design/methodology/approachThe paper draws on literature about gender and organizations to identify reasons for the persisting stereotype of women's risk aversion. Utilizing literature and concepts about risk appet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(145 citation statements)
references
References 68 publications
5
135
2
3
Order By: Relevance
“…Our findings on differences related to greater male predisposition to risk taking lend support to early research on gender and risk taking (see for example Harris et al, 2006). However, they do not support findings from the more recent research (see for example Maxfield et al, 2010).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Our findings on differences related to greater male predisposition to risk taking lend support to early research on gender and risk taking (see for example Harris et al, 2006). However, they do not support findings from the more recent research (see for example Maxfield et al, 2010).…”
Section: Discussioncontrasting
confidence: 55%
“…Our findings strongly suggest that youth entrepreneurship is not gender-bias and that both men and women reported similar potentials. This lends support to a number of studies (Kourilskva, & Walstad, 1998;Veciano et al, 2005;Wilson et al, 2007;Maxfield et al, 2010), but does not support the findings of studies conducted in similar cultural contexts to ours (see for example El Harbi et al, 2009;Zaidatol & Afsaneh, 2009). …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Women are more willing than men to adopt a fashion innovation earlier than other consumers-a risky consumer behavior (Workman & Cho, 2012) and are more likely than men to purchase products impulsively (Chen, 2001). Other research (that did not examine risk related to purchasing apparel) found that women (compared with men) are more open to uncertain and unstructured contexts (Maio & Esses, 2001;Washburn, Smith, & Taglialatela, 2005), are disinclined to take risks (e.g., Wagner, 2001) or that men and women did not differ in tendency for risk taking (e.g., Maxfield et al 2010). Research has found that women score higher than men on brand sensitivity (Beaudoin & Lachance, 2006;Warrington & Shim, 2000) and brand consciousness (Workman & Lee, 2013).…”
Section: Gender and Consumer Behaviourmentioning
confidence: 99%
“…Role incongruence may penalize those women who, counter to gender-based expectations, engage in high-risk activities (Maxfield et al 2010). Well-educated parents are, on the whole, better able than others to determine the degree of risk in a given situation and explain it to their children, who consequently will be relatively risk tolerant.…”
Section: Related Literature and Hypothesesmentioning
confidence: 99%